Modeling and control synthesis of a robotic manufacturing workcell - Ho, Edwin Hui Leong. (2008)
A "reconfigurable" robotic workcell currently under development at Nanyang Technolog-ical University consists of a group of devices which are made up of components that can be assembled into different robot configurations. The design of the workcell emphases on modularity to enable rapid reconfiguration of its devices and its layout for different pro-duction process. The reconfigurable features are important in the modern manufacturing environment as there is always a constant need to adapt the manufacturing system to the rapid changes in the market. This thesis focuses on the development of a software program for the supervisory control of the robotic workcell's operation. The objective of the supervisory control is to govern the workcell operations so that they comply to a set of user-defined specifications (i.e., "rules" in carrying out the workcell's operation). The developed software, known as CENSUP, consists of two main functions -designing of the workcell's control logic and implementing the control logic on the actual workcell. CENSUP is developed to allow graphically modeling of the workcell's operations and to formulate a control logic which will govern the workcell's operations in observing certain specifications. The generation of supervisory control is based on the general approach of supervisory control of discrete event systems (initiated by Ramadage and Wonham) that provides a formal framework for both centralized and distributed control development. The functionality of CENSUP is based on the architecture of centralized control, i.e., CENSUP is capable of implementation only centralized supervisory control. However, the thesis will also discuss the conditions for distributed control; stand-alone functions are incorporated in CENSUP to verify these conditions on the control logic.